Nigam’s hybrid intraperitoneal onlay mesh technique: an ideal procedure for big ventral hernia in an obese patient with hanging abdominal wall – a case report - Nigam, Vinod K.; Nigam , Siddharth (International Surgery Journal, 2026)
Nigam’s hybrid intraperitoneal onlay mesh technique (NH-IPOM) for big ventral hernia in an obese patient is the ideal surgical procedure. NH-IPOM is ideal for large incisional hernias specially in obese individuals where the redundant abdominal wall is hanging down. Incisional hernia repair is a common but troublesome problem develops after laparotomy for various reasons. Repair of incisional hernia is difficult as well as complicated specially in large hernia. It is operated by laparoscopic and open technique. Common methods of laparoscopic repair of incisional hernia are IPOM, IPOM-plus and hybrid-IPOM. Hybrid-IPOM is a combination of open and laparoscopic methods. We have developed our hybrid-IPOM technique, called NH-IPOM technique which is a combination of laparoscopic and open surgery. NH-IPOM is ideal for large incisional hernias specially in obese individuals where the redundant abdominal wall is hanging large hernia is excised and wound is closed. NH-IPOM is ideal procedure for such hernias due to low rate of complications including recurrence. NH-IPOM technique is easy and curative, but requires more studies.